Exploring the users’ experience in healthcare services - Rodrigues, Rita (2017)
The challenge in Healthcare services concerns the development of an agreeable experience to the users without affecting the functionality of the service. The traditional approach of the facilities design is focused on providing the best care with the most functional service possible. Based on this paradigm, most of the times the users and their experiences and emotions are not considered when a service is designed. However, concerns with the users’ experience in services are growing, and mainly in Portugal we are starting to observe that the Institutions intend to improve and ameliorate their facilities in order to meet the users’ needs. The project described in this article was developed in one of the biggest Healthcare Institutions in the north of Portugal: Hospital de São João at Porto city. In this project, the main intention of the research was to understand which elements of the physical setting of the Institution had the most impact on the users’ experience and perceptions of the service under study. The methodologies applied to gather the data were questionnaires (applied to the patients of the institution), unstructured interviews (conducted with healthcare professionals) and direct observations performed in situ. The results revealed that the most problematic elements identified were the poor designed signage system that resulted in wayfinding difficulties for the users.